ANALISIS FINANSIAL PRODUKSI YUWANA KERAPU MACAN (Epinephelus fuscoguttatus ) DENGAN PAKAN PELET KOMERSIAL DAN IKAN RUCAH DALAM KERAMBA JARING APUNG - Tatam Sutarmat (Jurnal Perikanan Universitas Gadjah Mada, 2005)
This study aimed to evaluate financial analysis of fingerling production of tiger grouper (Epinephelus fuscoguttatus) fed commercial pellet and trash fish. The experiment was carried out in floating net cages located in the Gondol Research Institute for Mariculture Bali. A total of 3,000 humpback grouper juveniles with the average body weight of 12 g and 8 cm of total length, were stocked in six 2x2x2 m cages at stocking densities of 500 fishes/cage. The cages were divided in two groups for two treatments in triplicates. The treatments were feeding with commercial pellet and copper raw trash fish. Results showed that  body weight gain, total length, specific growth rate, were not significant different (P>0.05) between fish fed commercial pellet and trash fish. Feed conversion ratios obtained by commercial pellet and trash fish were 1.43 and 4.53, respectively. Survival rates were significant different (P<0.05) between fish fed commercial pellet and trash fish which were 83.33 and 69.86%, respectively. Nursering for production of tiger grouper fingerling fed either commercial pellet or trash fish in floating net cage were economically feasible. Feeding with commercial pellet gave a higher net profit of Rp 4,486,250.- with the RC ratio of 1.47 and rentability of 47.12%, while feeding with trash fish gave a net profit of Rp 3,212,500.- with the RC ratio of 1.37 and rentability of  37.35%.This study aimed to evaluate financial analysis of fingerling production of tiger grouper (Epinephelus fuscoguttatus) fed commercial pellet and trash fish. The experiment was carried out in floating net cages located in the Gondol Research Institute for Mariculture Bali. A total of 3,000 humpback grouper juveniles with the average body weight of 12 g and 8 cm of total length, were stocked in six 2x2x2 m cages at stocking densities of 500 fishes/cage. The cages were divided in two groups for two treatments in triplicates. The treatments were feeding with commercial pellet and copper raw trash fish. Results showed that  body weight gain, total length, specific growth rate, were not significant different (P>0.05) between fish fed commercial pellet and trash fish. Feed conversion ratios obtained by commercial pellet and trash fish were 1.43 and 4.53, respectively. Survival rates were significant different (P<0.05) between fish fed commercial pellet and trash fish which were 83.33 and 69.86%, respectively. Nursering for production of tiger grouper fingerling fed either commercial pellet or trash fish in floating net cage were economically feasible. Feeding with commercial pellet gave a higher net profit of Rp 4,486,250.- with the RC ratio of 1.47 and rentability of 47.12%, while feeding with trash fish gave a net profit of Rp 3,212,500.- with the RC ratio of 1.37 and rentability of  37.35%.